2014
DOI: 10.1111/pan.12397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sevoflurane anesthesia on brain oxygenation in children younger than 2 years

Abstract: Despite a significant decrease of MAP, 1 MAC of sevoflurane induced a significant increase in regional brain oxygenation. But subgroup analysis showed that MAP decrease had a greater impact on brain oxygenation, in children younger than 6 months. According to our results, MAP value during anesthesia should not go under 33 mmHg in children ≤6 months and 43 mmHg in children >6 months, as further changes in MAP, PaCO2 or hemoglobin during anesthesia may be poorly tolerated by the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 26 publications
(31 reference statements)
3
47
0
3
Order By: Relevance
“…Nonetheless, a recent study described positive association of intraoperative blood pressure and rSO 2 c values in a cohort of anesthetized infants up to 3 months of age [11]. In anesthetized patients, O. Rhondali et al found that the higher the absolute MAP was during anesthesia, the higher the rSO 2 c was [6, 7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, a recent study described positive association of intraoperative blood pressure and rSO 2 c values in a cohort of anesthetized infants up to 3 months of age [11]. In anesthetized patients, O. Rhondali et al found that the higher the absolute MAP was during anesthesia, the higher the rSO 2 c was [6, 7]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Kasman N and Brady K in a review article summarized the existing evidence relating cerebral desaturation events to neurological outcome in children who had undergone cardiac surgery [5]. A few recent studies addressed the issue of adequate blood pressure based on cerebral oxygenation monitoring in children under inhaled general anesthesia with sevoflurane [6, 7]. But, so far, there is no sufficient evidence to support the routine use of NIRS during general surgical procedures in children.…”
Section: Introductionmentioning
confidence: 99%
“…[31527] We found an SO 2 < 5% reduction in brain tissue saturation in children during routine laparoscopy; thus long-term neurological outcome should be evaluated in children and particularly in infants whose cerebral metabolic reserve seems to be lower and poorly tolerated by the brain. [2829]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pediatric patients might be at risk for cerebral ischemia or hyperemic injury when blood pressure crosses below the lower limit of autoregulation, or exceeds the upper limit of autoregulation, respectively [45,46 & ]. Particularly neonates are at considerable risk of physiological disturbances, eventually leading to neurologic impairment [47,48]. These issues inquire about how to select safe hemodynamic goals in children.…”
Section: Pediatric Surgerymentioning
confidence: 99%
“…However, few recent studies have described the use of NIRS in children during noncardiac surgery. Rhondali et al [45,48] used NIRS to assess the impact of sevoflurane and anesthesia-induced hypotension on brain perfusion. An observational study in infants treated for esophageal atresia indicated that NIRS represents a good monitor of hemodynamic changes, and might therefore guide perioperative care [49 & ].…”
Section: Pediatric Surgerymentioning
confidence: 99%